FRAMING ANALYSIS OF AGUS BUNTUNG CASE COVERAGE IN INDONESIAN ONLINE MEDIA - Syukron, Muhammad; Akbar, Muh.; Sonni, Alem Febri (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
The increasing coverage of sexual violence cases in Indonesian online media reflects the power of the media in shaping public opinion. One of the cases in the spotlight was the reporting of Agus Buntung, a man with a disability who became a suspect in an alleged sexual assault. This study aims to analyse how the three largest online media in Indonesia, Tribunnews.com, Kompas.com, and Jawapos.com, framed the news of the Agus Buntung case, focusing on the application of the Pan & Kosicki framing model and its relevance to journalistic ethics. This research uses a descriptive qualitative approach with Pan & Kosicki's framing analysis method, which includes four structures: syntax, script, thematic, and rhetorical. Data sources were three headlines from each media, selected based on popularity and dominant narrative content. Each news story was analysed based on the framing tools and evaluated against journalistic ethical principles, such as balance (cover both sides), accuracy, non-discrimination, and protection of vulnerable groups, in this case people with disabilities. The results showed that the three media framed the case with a point of view that tended to corner the perpetrator, with variations in framing intensity. Tribunnews.com uses a sensational and dramatic writing style that is disproportionate to the perpetrator's condition as a person with a disability, and often uses terms that suggest negative labelling. Kompas.com emphasised the statement of the legal apparatus, but still mentioned the disability label without the context of protection. Meanwhile, Jawapos.com tried to present two sides of the narrative, but still lacked space to provide clarification from the perpetrator or his legal counsel. These findings show a tendency to violate journalistic ethics in the three media, especially in the aspects of presumption of innocence, balance, and treatment of vulnerable groups. Media framing shapes social reality that influences public perception in an emotional and non-neutral manner, as explained in Berger and Luckmann's social construction theory